2017
DOI: 10.3758/s13428-017-0898-2
|View full text |Cite
|
Sign up to set email alerts
|

Scoring best-worst data in unbalanced many-item designs, with applications to crowdsourcing semantic judgments

Abstract: Best-worst scaling is a judgment format in which participants are presented with a set of items and have to choose the superior and inferior items in the set. Best-worst scaling generates a large quantity of information per judgment because each judgment allows for inferences about the rank value of all unjudged items. This property of best-worst scaling makes it a promising judgment format for research in psychology and natural language processing concerned with estimating the semantic properties of tens of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(90 citation statements)
references
References 37 publications
0
90
0
Order By: Relevance
“…This process was repeated 128 times to create the master stimulus set over which participants would make best-worst judgments. Four-tuples were created according to the design suggestions laid out by Hollis (2017): (1) no two words appeared together in more than one 4-tuple, (2) every word appeared in an equal number of 4-tuples, and (3) no 4-tuple was viewed more than once across all participants. These features each increase the amount of information gained per judgment made.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This process was repeated 128 times to create the master stimulus set over which participants would make best-worst judgments. Four-tuples were created according to the design suggestions laid out by Hollis (2017): (1) no two words appeared together in more than one 4-tuple, (2) every word appeared in an equal number of 4-tuples, and (3) no 4-tuple was viewed more than once across all participants. These features each increase the amount of information gained per judgment made.…”
Section: Methodsmentioning
confidence: 99%
“…Scoring best-worst data A detailed explanation of the various ways to convert best-worst data into estimates of latent dimensions (i.e., scoring methods), along with their respective benefits and shortcomings, is provided by Hollis (2017). For the current analysis, each of the five scoring methods described in Hollis (2017) were applied to each of the four latent dimensions being estimated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Gold questions were annotated more than eight times. 13 More complex optimization algorithms exist, such as those described in (Hollis, 2018); however, our past experiments showed that the simple counting procedure obtained the most reliable results.…”
Section: Reliability Of Data Annotationsmentioning
confidence: 99%